Social media usage and depressive symptoms among Icelandic adolescents : the effect of body image and gender - Árdís Eva Friðriksdóttir 1993- (2019)
The most popular activity on the Internet among adolescents is social media and they spend a large proportion of their time on it. This extensive use has left parents and educators worried about the effects it has on adolescent’s development, and whether they should encourage or not. The current study examined the relationship between social media usage, body image and depressive symptoms among adolescent females and males in Iceland. Data in this study comes from Youth in Iceland 2016, a cross-sectional survey conducted by ICSRA. A random sample of 2,106 elementary students in the eighth, ninth and tenth grade was used, with 1,014 males and 1,067 females. Participant’s age ranged from 12 to 17 years. The results showed that social media usage and negative body image were associated with depressive symptoms, and social media usage was associated with negative body image. Indirect effect of social media usage on depressive symptoms through body image was significant, and the effect was stronger among females than males. The findings indicate that body image is a mediator in the relationship between social media usage and depressive symptoms among adolescents, especially among female adolescents. Keywords: Social media usage, adolescents, depressive symptoms, body image, body dissatisfaction, gender difference Vinsælasta afþreying unglinga á netinu eru samfélagsmiðlar og eyða þeir miklum tíma í notkun þeirra. Þessi mikla notkun hefur valdið áhyggjum og spurningum meðal foreldra og kennara um áhrif þeirra á mótun unglinga og hvort þeir ættu að hvetja notkunina eða ekki. Þessi rannsókn skoðaði sambandið milli samfélagsmiðlanotkunar, líkamsímyndar og þunglyndiseinkenna á meðal unglingsstelpna og stráka á Íslandi. Gögn voru fengin frá þverfaglegri rannsókn á vegum Rannsóknar og greiningar úr spurningalistanum Ungt fólk 2016. Tilviljunarúrtak með 2.106 grunnskólanemendum í áttunda, níunda og tíunda bekk var notað, þar af voru 1.014 strákar og 1.067 stelpur. Aldur þátttakanda var á bilinu 12 til 17 ár. Niðurstöður ...